Mandated Diocesan Centralized Financial Service: Canon 1276 - King, William Joseph (CLSA advisory opinions, 2001-2005, 2001)
May a diocesan bishop licitly require that all parishes participate in centralized financial services provided and administered by the diocese, such as investment management, payroll services, and even accounts payable?